2019
DOI: 10.1166/jbt.2019.2142
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Stability of Artificial Prosthesis Performance for Hip Replacement

Abstract: The hip replacement is beneficial to relieve joint pain and misfunction. We previously designed the model to monitor the stability of the artificial prosthesis during the surgery based on the resonance frequency (RF), which is a non-invasive and sensitive technique. In this study, we further applied the techniques to monitor its use in hip replacement and compared the effect in individuals. Our data have showed that resonance frequency is very promising for the analysis of stability of artificial prosthesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…IFN-γ also has immunomodulatory, antiviral, and antitumor functions. It has been reported that IFN-γ can effectively activate chemokine receptors and recruit neutrophils to the liver, leading to an inflammatory response (Shimoyama et al, 2021) and other molecular signaling (Chen et al, 2019, 2020; Liao et al, 2022; Zhang et al, 2019). Hepatocyte injury and necrosis have been reported in DMAc-exposed animal models (Wang and Chen, 2020), which cannot be excluded from the role of IFN-γ.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ also has immunomodulatory, antiviral, and antitumor functions. It has been reported that IFN-γ can effectively activate chemokine receptors and recruit neutrophils to the liver, leading to an inflammatory response (Shimoyama et al, 2021) and other molecular signaling (Chen et al, 2019, 2020; Liao et al, 2022; Zhang et al, 2019). Hepatocyte injury and necrosis have been reported in DMAc-exposed animal models (Wang and Chen, 2020), which cannot be excluded from the role of IFN-γ.…”
Section: Discussionmentioning
confidence: 99%